Changes in serum pepsinogen levels and their value as a predictor of treatment outcomes in children with peptic ulcer. (19th January 2019) - Zhou, Bin; Chen, Xintao; Huang, Biao; Hu, Yonghong; Tang, Guorong; Zhang, Jue; Lin, Qiong
Abstract : Aim: To investigate pepsinogen secretion from the neonatal stage to childhood and its diagnostic value for peptic ulcer (PU) in children. Methods: In this study, 2114 'healthy' children and 51 children with PUs undergoing a medical examination by gastroscopy were selected as subjects. The serum content of pepsinogen I (PGI) and serum pepsinogen II (PGII) was tested for each of the subjects using time‐resolved fluorescence immunoassay, which is characterised by high sensitivity and a wide measuring range. Results: The serum PGI and PGII levels were found to increase with age, becoming stable and similar to those of adults at the age of 16. In 51 children with PUs, PGI was 201.03 ± 30.74 ng/mL before treatment and 187.92 ± 19.86 ng/mL after treatment ( P > 0.05); PGII was 17.36 ± 1.47 ng/mL before treatment and 17.20 ± 3.98 ng/mL after treatment ( P > 0.05). Conclusions: It is difficult to establish the normal range of PG in children owing to its variance by age. However, if the normal reference range for individual age groups is known, it may still serve as a useful diagnosis system as well as a detecting indicator during the course of PU treatment. There are significant differences in PGI expression in children with PU before and after PU is cured, whereas other indicators show no differences before and after treatment.